Luminescence from germanium and germanium on silicon - Arguirov, Tzanimir; Kittler, Martin; Oehme, Michael; Abrosimov, Nikolay V.; Vyvenko, Oleg F.; Kasper, Erich; Schulze, Jörg (Solid State Phenomena, 2014)
We present an overview on generation of direct gap photo-and electroluminescence in Ge bulk wafers, Ge thin films deposited on Si, and Ge p-i-n diodes prepared on Si substrates. We analyzed the emission in a spectral range from 0.45 eV to 0.95 eV, covering the radiation caused by direct gap transitions, the indirect one, and also the luminescence related to transition on dislocations. The temperature and excitation level strongly influence the intensities of direct and indirect photoluminescence in bulk samples. As it could be expected, high temperature and excitation favour the generation of direct gap luminescence. Intrinsic bulk Ge shows a quadratic dependence of the direct gap luminescence on the excitation and a sub-quadratic one for the indirect. The photoluminescence spectra taken from intrinsic Ge on Si layers show features related to dislocations. There are two spectral regions associated with dislocation recombination. At room temperature one is at around 0.45 eV and the other at 0.72 eV. We found strong direct gap radiation from the Ge p-i-n diodes with intrinsic, highly dislocated active area (dislocation density of about 108-1010 cm-2). There is a threshold current density of 8 kA/cm2, at which the direct band luminescence becomes a super-quadratic. The dependence of the radiation intensity on the excitation is governed by a power law with exponent of 1.7 before reaching that threshold and 4.5 after exceeding it. Above the threshold the dislocation radiation shows similar dependence on the excitation as the direct band luminescence. © (2014) Trans Tech Publications, Switzerland.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Dislocations; Ge; Ge on Si; LED; Luminescence